Examination of pathological process pecularities caused by A/duck/Altai/469/14 H5N1 isolate of avian influenza virus in chickens - V. Yu. Sosipatorova; D. A. Altunin; M. A. Tsivanyuk; I. A. Chvala (Ветеринария сегодня)
Data on examination of chickens intranasally infected with А/duck/Altai/469/14 H5N1 isolate of avian influenza virus for clinical signs and microscopic and gross pathomorphological lesions in their organs are given in the paper. The virus antigen was identified in chicken tissue lesions by immunohistochemical method.